9‐3: BLA LTPS TFTs based μ‐LED Display with Integrated Digital Driving. Issue 1 (29th May 2019) - Chen, Yuanfeng; Kim, Hyo-Min; Lee, Suhui; Jeong, Duk Young; Jung, Younghun; Lee, Sang Hem; Jeong, Tak; Joo, Jaeyoung; Hut, Jeongwook; Choi, Jong Hwa; Kwak, Joon Seop; Geng, Di; et al.
Abstract : We propose a blue laser annealed (BLA) LTPS TFT based μ‐LED display with integrated gate driver and digital data driver. The BLA LTPS TFTs are fabricated using a blue diode laser based lateral crystallization method, which reduces the cost compare to ELA process while offering higher mobility for high current driving. The integrated gate driver and digital data driver enable simplified driving scheme, which further reduces the cost for external driver ICs. Together with the μ‐LEDs which offer high brightness over 40, 000 cd/m 2, the fabricated 32 x 32 μ‐LED display demonstrates potential approach for smart headlamp and intelligent lighting applications.